A solid ultrasonic coupling membrane for superficial vascular ultrasonography. Issue 9 (17th February 2022) - Sun, Di; Liu, Jie; Xue, Lijuan; Li, Li; Xie, Daoyin; Li, Shilin; Li, Shengmei; Wang, Xinlian; Yin, Dongtao; Ren, Zhaoqi; Bai, Ru; Guo, Wei; et al.
Abstract : Clear intravascular ultrasound images with various brand of ultrasound instruments can be acquired using PAM-BCs. Polyacrylamide was enhanced by bacterial nanocellulose. PAM-BCs can be used as the ultrasonic coupling material for the diagnosis of superficial disease. Abstract : Superficial thrombophlebitis is one of the most significant complications of superficial vein thrombosis. Rapid imaging and mapping with high resolution is particularly important for accurate diagnosis so as to carry out treatment as soon as possible. Ultrasound imaging technology has been used extensively because of the low-cost, minimal invasiveness, and convenient application in clinical practice. And the ultrasonic couplant is an essential component in ultrasound examination. However, when imaging superficial structures, traditional liquid ultrasonic couplants often produce inadequate results. In this study, we investigate whether a hydrogel membrane can be used to improve the imaging of superficial vessels. To this end, we generated a polyacrylamide-bacterial nanocellulose hydrogel membrane (PAM-BC) that efficiently forms at 60 °C in only 10 min by redox polymerization. With PAM-BC-2.5, it was possible to acquire high resolution intravascular ultrasound images to assess superficial vessels in humans and the superficial vasculature in rats and miniature pigs using various brands of ultrasound instruments. The PAM-BCs represent a new, solid ultrasonic membrane which is suitable for diagnosing disease in superficial vessels.